Antiphospholipid Antibodies in Pregnancy: Maternal and Neonatal Implications - Gris, Jean-Christophe; Guillotin, Florence; Chéa, Mathias; Bourguignon, Chloé; Nouvellon, Éva; Bouvier, Sylvie (Seminars in Thrombosis and Hemostasis, 2022)
Antiphospholipid antibodies (aPL Abs) have long been associated with the occurrence of certain specific pregnancy morbidities, affecting both mother and fetus. Antithrombotic-based prophylactic regimens are the standard of care. Their intensity is modulated by the thrombotic history and has greatly improved the prognosis related to spontaneous morbidity. Observational studies show that this treatment is still associated with the persistence of excess of late-pregnancy placental diseases, calling for new or complementary developments, yet to be validated. Rigorous prospective multicentric validation of clinical and laboratory parameters capable of identifying those women and fetuses at a risk of pejorative evolution, thus early prognosis, is a priority issue. These will make it possible to develop customized treatments and test them. Furthermore, there are still concerns, particularly neurodevelopmental ones, about children born to aPL Ab-positive mothers, and clarification based on regular, more systematic evaluations is required. Even after pregnancy, women with a pure obstetrical antiphospholipid syndrome are at a greater risk of venous and arterial thrombosis over time, and prevention needs to be improved. These women also appear to develop more psychiatric and mood disorders. Central nervous system imaging using high-resolution techniques has shown subtle impairments in the white matter, associated with the most pathogenic aPL Abs and the clinical significance of this is under investigation. These mothers also seem to develop an excess of cancers. The systemic impact of aPL Abs is gradually being suspected, although this requires further evidence, and prevention should be envisaged.
Keywords: antiphospholipid antibodies; pregnancy; placental disease; mother; neonate; thrombosis; psychiatric; cancer